Biomasse et stocks de carbone des forêts tropicales africaines (synthèse bibliographique) - Loubota Panzou, Grâce Jopaul; Doucet, Jean-Louis; Loumeto, Jean-Joël; Biwole, Achille; Bauwens, Sébastien; Fayolle, Adeline (Biotechnologie, agronomie, société et environnement, 2016)
Introduction. Quantifying the biomass and carbon stocks contained in tropical forests has become an international priority for the implementation of the REDD+ mechanism. Forest biomass is estimated at three successive levels: the tree, the stand and the region level. This paper reviews the state of the art regarding the estimation of biomass and carbon stocks in tropical African forests. Literature. This review highlights the fact that very few allometric equations, equations used for estimating the biomass of the tree using non-destructive measurements (diameter, height), have been established for tropical African forests. At the stand level, the review highlights the spatial and temporal variations in biomass between forest types in Central and Eastern Africa. While biomass recovery after a disturbance (logging, for instance) is rather quick, a great deal of uncertainty still remains regarding the spatial variation in biomass, and there is no consensus on a regional biomass map. The quality of biomass mapping in tropical Africa strongly depends on the type of remotely-sensed data being used (optical, RADAR or LIDAR), and the allometric equation used to convert forest inventory data into biomass. Conclusions. Based on the lack of precision of the available allometric equations and forest inventory data and the large spatial scale involved, many uncertainties persist in relation to the estimation of the biomass and carbon stocks contained in African tropical forests.